1964
DOI: 10.1128/aem.12.1.18-23.1964
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Direct Plating Media for the Isolation and Enumeration of Enterococci in Certain Frozen Foods1

Abstract: BURKWALL, _MARY K. (Iowa State University, Ames), AND PAUL A. HARTMAN. Comparison of direct plating media for the isolation and enumeration of enterococci in certain frozen foods. Appl. MIicrobiol. 12:18-23. 1964.-A total of 15 agar media were examined for their yield, selectivity, readability, and simplicity of preparation and use. A thallium medium of Barnes was selected as the better of the high yield-fair selectivity type of medium and an azide-citrate medium of Reinbold appeared to be the better of the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1966
1966
2012
2012

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Evaluation of the efficiency of several media previously proposed for enterococci have shown several problems; the medium suggested by Barnes (1965) required much experience and expertise for distinction between S. fuecium and S. fueculis, and that described by Mead (1963) yielded very low recoveries with freeze injured cultures. KF medium was found most efficient for the recovery of enterococci from frozen foods (Burkwall and Hartman 1964). We found that The relative density of chains comprised of a t least 3 cells in the total cell population of the cultures was determined microscopically ( Fig.…”
Section: Selective Medium For S Faecalissupporting
confidence: 80%
“…Evaluation of the efficiency of several media previously proposed for enterococci have shown several problems; the medium suggested by Barnes (1965) required much experience and expertise for distinction between S. fuecium and S. fueculis, and that described by Mead (1963) yielded very low recoveries with freeze injured cultures. KF medium was found most efficient for the recovery of enterococci from frozen foods (Burkwall and Hartman 1964). We found that The relative density of chains comprised of a t least 3 cells in the total cell population of the cultures was determined microscopically ( Fig.…”
Section: Selective Medium For S Faecalissupporting
confidence: 80%
“…The MBA medium of Schaedler et al (11) is a highly selective medium for the isolation of group D enterococci. It may be considered as a high selectivity-low yield type of medium (1). Such a medium is generally of limited value.…”
Section: Discussionmentioning
confidence: 99%
“…(1960) placed such strains in an 'enterococcus biotype ' group andMieth (1960,1961) placed such strains in an 'atypical enterococcus' group. Burkwall and Hartman(1964) also had t o designate an 'atypical enterococcus' group to accommodate many of the strains isolated in their study. (See also F e r r a r o , 1960.)…”
Section: Definition Of T E R M Smentioning
confidence: 99%